1990
DOI: 10.1128/jb.172.2.949-955.1990
|View full text |Cite
|
Sign up to set email alerts
|

Natural transformation in Campylobacter species

Abstract: Growing cells of Campylobacter coli and C. jejuni were naturally transformed by naked DNA without the requirement for any special treatment. Transformation frequencies for homologous chromosomal DNA were approximately 10(-3) transformants per recipient cell in C. coli and 10(-4) in C. jejuni. Maximum competence was found in the early log phase of growth. Campylobacters preferentially took up their own DNA in comparison with Escherichia coli chromosomal DNA, which was taken up very poorly. Three new Campylobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
283
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(294 citation statements)
references
References 30 publications
9
283
1
1
Order By: Relevance
“…T o clone the regions flanking the gene encoding the putative siderophorebinding protein a plasmid rescue method was used. The plasmid pSP120 was introduced into C. coli UA585 by natural transformation (Wang & Taylor, 1990) and tetracycline-resistant transformants were recovered. As the plasmid is not capable of extrachromosomal replication the only way for this antibiotic-resistant phenotype to arise is if the plasmid becomes integrated into the chromosome by a single point crossover driven by homologous recombination at the region of homology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T o clone the regions flanking the gene encoding the putative siderophorebinding protein a plasmid rescue method was used. The plasmid pSP120 was introduced into C. coli UA585 by natural transformation (Wang & Taylor, 1990) and tetracycline-resistant transformants were recovered. As the plasmid is not capable of extrachromosomal replication the only way for this antibiotic-resistant phenotype to arise is if the plasmid becomes integrated into the chromosome by a single point crossover driven by homologous recombination at the region of homology.…”
Section: Resultsmentioning
confidence: 99%
“…Grant & S. F. Park, unpublished data). In this study we have identified the homologue in C. coli UA585, which is naturally competent and amenable to genetic manipulation (Wang & Taylor, 1990). Plasmid rescue was used to clone the DNA sequences flanking the gene encoding this protein from this strain.…”
Section: G T S N E a S V F D A R M Q S K R H L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the DNA was treated with 600 U of T4 DNA ligase (New England Biolabs) for 18 h at 16°C. The repaired transposed DNA was extracted with phenol-chloroform-isoamyl alcohol (25:24:1), pH 6.7, and ethanol precipitated prior to incubation with recipient C. jejuni NCTC 11168 cells and DNA uptake by natural transformation (89). Cells containing EZ-Tn5-Cm were selected by being plated on MH agar plates containing 20 g ml Ϫ1 Cm.…”
Section: Methodsmentioning
confidence: 99%
“…C. jejuni F38011 was transformed with pGEMTcj1000aph by electroporation and the resulting transformants were selected on kanamycin plates and confirmed by PCR. Genomic DNA was extracted and used for natural transformation of C. jejuni NCTC11168 (Wang & Taylor, 1990b). The cj1000 : : aph mutant construction was confirmed by PCR and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%